2020
DOI: 10.1002/adfm.202003934
|View full text |Cite
|
Sign up to set email alerts
|

Epitope‐Imprinted Nanoparticles as Transforming Growth Factor‐β3 Sequestering Ligands to Modulate Stem Cell Fate

Abstract: Growth factors (GFs) are biomolecules with potent biological effects but inherent limitations hinder their potential as therapeutic agents and cell culture supplements in tissue engineering and regenerative medicine (TERM). Biomaterials that sequester endogenous GFs by affinity binding might circumvent such limitations and thus are being increasingly investigated. Here, molecularly imprinted nanoparticles (MINPs) are proposed as specific abiotic ligands for GFs. As a proof of concept, a conformational epitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…Our laboratories have come up with novel methods for the production of materials capable of binding and recognizing specific proteins (44)(45)(46). To minimize the diffusive limitation of a material imprinted in the bulk, we have focused on surface adsorption (47)(48)(49). Correspondingly, our methods have been designed for the production of micro-or nanoparticles (NPs), to produce materials with large surfaceto-volume ratios.…”
Section: What Are the Challenges Of Imprinting Large Biomacromolecules?mentioning
confidence: 99%
See 3 more Smart Citations
“…Our laboratories have come up with novel methods for the production of materials capable of binding and recognizing specific proteins (44)(45)(46). To minimize the diffusive limitation of a material imprinted in the bulk, we have focused on surface adsorption (47)(48)(49). Correspondingly, our methods have been designed for the production of micro-or nanoparticles (NPs), to produce materials with large surfaceto-volume ratios.…”
Section: What Are the Challenges Of Imprinting Large Biomacromolecules?mentioning
confidence: 99%
“…To these ends, we have developed a surface imprinting technique whereby the template molecule is adsorbed at the interface between two distinct phases. Agitation during polymerization results in the formation of droplets, with subsequent polymerization yielding microparticles or NPs (48).…”
Section: What Are the Challenges Of Imprinting Large Biomacromolecules?mentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the nanoparticles could selectively bind the GF both in noncompetitive assays and in complex human fluid (platelet lysate). Human adipose stem cells, when incubated with platelet lysate and the imprinted nanoparticles, resulted in a higher collagen matrix deposition when compared to the control (non-imprinted nanoparticles) [ 111 ].…”
Section: Molecular Imprinting For Te Applicationsmentioning
confidence: 99%